Honor among Chiefs: An Experiment on Monitoring and Diversion Among Traditional Leaders in Malawi. Issue 8 (2nd August 2020) - Carlson, Elizabeth; Seim, Brigitte
Abstract: Traditional, hereditary chiefs are an integral part of the development infrastructure in many African countries. To capture chiefs' behaviour as agents of development and understand the accountability mechanisms they face, we conduct a field experiment with 200 Malawian village chiefs, documenting how they distribute a valuable development good – iron roofing sheets – as we sequentially add monitoring by donors, subjects, and the state. We find evidence that even in the absence of formal accountability institutions, chiefs are responsive to monitoring by all principals. However, principals have competing demands: while most principals prefer allocations based on need as classified by the local community, a subset of the chief's subjects – his relatives – prefer to receive sheets themselves, regardless of need. When subjects are informed about the availability of sheets, relatives are able to capture allocations, overriding other principals and causing discontent. Altogether, diversion is minimised when chiefs are monitored by the donor, and only the donor. When chiefs are monitored by all their principals simultaneously, diversion is not significantly lower (compared to control), but dissatisfaction among subjects is greater. This study adds to the literature on chieftaincy and highlights the role of common agency in the design and analysis of development interventions.